2010
DOI: 10.1002/jor.21171
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic induction heating of an orthopaedic nickel–titanium shape memory device

Abstract: Shape memory orthopaedic implants made from nickel-titanium (NiTi) might allow the modulation of fracture healing, changing their cross-sectional shape by employing the shape memory effect. We aimed to show the feasibility and safety of contact-free electromagnetic induction heating of NiTi implants in a rat model. A water-cooled generator-oscillator combination was used. Induction characteristics were determined by measuring the temperature increase of a test sample in correlation to generator power and time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…For instance, in the first few weeks in vivo after initial stabilization, 5 this mechanical change would have to depend on the type of fracture, its location and co-morbidities. 14 It will be the goal of future studies to specify reliable recommendations of the variance of these parameters on plate stiffness. The results to be determined would provide the recommendations in a clinical setting to best know when and how much the stiffness of fixation should be altered to promote the best healing outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the first few weeks in vivo after initial stabilization, 5 this mechanical change would have to depend on the type of fracture, its location and co-morbidities. 14 It will be the goal of future studies to specify reliable recommendations of the variance of these parameters on plate stiffness. The results to be determined would provide the recommendations in a clinical setting to best know when and how much the stiffness of fixation should be altered to promote the best healing outcome.…”
Section: Discussionmentioning
confidence: 99%
“…11 Changing the construct rigidity of such devices over the course of fracture healing could promote accelerated healing as well as avoiding additional invasive procedures. 14 The goal of this study was to measure the stiffness changes of Nitinol implants of different design before and after transformation, i.e. after initiation of the one way shape memory effect (SME).…”
Section: Introductionmentioning
confidence: 99%
“…Similar experiments were shown by Mohr et al as they used the inductive heating (f = 258 kHz) of magnetic nanoparticles in thermoplastic polymers [10]. Short time heating of cylindrically NiTi-SMAs in biological tissue (f = 250 kHz), has been shown by Müller et al [30]. General problems of this method can be seen in the direct exposition of living tissue to high-frequency fields resulting in an unintended heating of the tissue (e.g.…”
Section: Inductive Heating Of Shape Memory Devicesmentioning
confidence: 73%
“…It was shown that the temperature-controlled in-vivo heating of cylindrically NiTi test specimens causes only marginal effects on biological tissue [3]. It was shown that the temperature-controlled in-vivo heating of cylindrically NiTi test specimens causes only marginal effects on biological tissue [3].…”
Section: Resultsmentioning
confidence: 99%